Psychoeducation of Academic Procrastination in Undergraduate Students - Setiyono, Gilang Agus; Paramita, Riyangka; Hartini, Nurul (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Academic procrastination is the tendency always or almost always to postpone work on academic assignments and always or almost always experience disturbing anxiety related to the academic procrastination carried out. Academic procrastination negatively impacts a student's life in the academic, physical and social fields. Therefore, it is necessary to implement psychoeducation to prevent and intervene in academic procrastination in students, especially those at an advanced level. This psychoeducational activity aims to map the level of procrastination of advanced students at the ABC Department, XYZ Faculty, X University and increase students' understanding of academic procrastination. The subjects of this research were 138 Semester 6 students at the ABC Department, XYZ Faculty, X University. The method used is a survey using the Aitken Procrastination Inventory procrastination measuring instrument. Changes in student understanding were measured through pre-test and post-testpost-test, then analyzed using the T-test. From the results of observations, it is known that as many as 4 students (2.9%) were at the